Resistance exercise stress: theoretical mechanisms for growth hormone processing and release from the anterior pituitary somatotroph - Hymer, W. C.; Kraemer, W. J. (European Journal of Applied Physiology, 2023)
Heavy resistance exercise (HRE) is the most effective method for inducing muscular hypertrophy and stimulating anabolic hormones, including growth hormone, into the blood. In this review, we explore possible mechanisms within the GH secretory pathway of the pituitary somatotroph, which are likely to modulate the flow of hormone synthesis and packaging as it is processed prior to exocytosis. Special emphasis is placed on the secretory granule and its possible role as a signaling hub. We also review data that summarize how HRE affects the quality and quantity of the secreted hormone. Finally, these pathway mechanisms are considered in the context of heterogeneity of the somatotroph population in the anterior pituitary.